KUALITAS LIMBAH CAIR EKSTRAKSI SAGU (Metroxylon Sp.) MENGGUNAKAN ALAT PENYARING SISTEM BERLAPIS PADA BEBERAPA WAKTU PENYIMPANAN - Sarman Oktovianus Gultom; Paulus Payung; Jefri Yawan (AGROINTEK, 2016)
In order to produce sago starch, sago bar had to be crushed and extracted using water to separate starch from other compounds. In the sago processing, a lot of water was used to extract sago starch and finally was discarded as liquid waste. In this study, the quality of sago liquid waste, before and after applying a layer-based filter containing: coir, charcoal, gravel and sand, was measured. The study was designed with a different time of storage of the Sago liquid waste, namely 0,1,2,3,4, and 5 day of storage. Each day the liquid waste was filterd using layer-based filter, and then the quality of the liquid waste was compared. The parameters measured were total suspended solids, total dissolved solids, final pH, and physical parameters such as smell and color. The results ofthis studyshowed that quality decrese of sago liquid waste accurs during 5 days of storage as indicated by increasing the total suspended solids (up to 1400 mg/L) and the dissolved solids (up to 2000 mg/L), decresing the pH value (down to 5) and arising unpleasant smells. Furthermore,the use of thelayer-basedfilterwas effective enoughto restorethe quality of the sago liquid water bydecreasing thetotalsolids, neutralizing thepH valueand reducingthe unpleasant smell